German crowd-investing platforms: Literature review and survey - David Grundy; Carolina Ohmer (Cogent Business & Management, 2016)
This article presents a comprehensive overview of the current German crowd-investing market drawing on a data-set of 31 crowd-investing platforms including the analysis of 265 completed projects. While crowd-investing market still only represents a niche in the German venture capital market, there is potential for an increase in both market volume and in average project investment. The market share is distributed among a few crowd-investing platforms with high entry barriers for new platforms although platforms that specialise in certain sectors have managed to successfully enter the market. German crowd-investing platforms are found to promote mainly internet-based enterprises (36%) followed by projects in real estate (24%) and green projects (19%), with the median money raised 100,000 euro.
Keywords: 650